Evaluation of biochar-derived carbocatalysts for pyrolytic conversion of sawdust: Life cycle assessment towards monophenol production. (15th December 2022) - Cao, Bin; Jiang, Ding; Zheng, Yijie; Fatemeh Rupani, Parveen; Yuan, Chuan; Hu, Yamin; Chen, Hao; Li, Chao; Hu, Xun; Wang, Shuang; Yuan, Jianping; Abomohra, Abdelfatah
Graphical abstract: Highlights: LCA of biochar-derived carbocatalysts (BDCs) was studied. BDCs were produced from seaweed, microalgae and lignocellulosic waste. BDCs promoted monophenols during sawdust pyrolysis. The maximum content of monophenols was 54.64% over seaweed-derived BDCs. Hydroxyl facilitate the production of monophenols by providing H radicals. Abstract: The present study aimed to prepare biochar-derived carbocatalysts (BDCs) from three feedstocks (seaweed, microalga and lignocellulosic biomass) and further evaluate the environmental impacts through life cycle assessment (LCA) methodology. It is indicated that the step of employing chemical activation agent had the highest environmental burdens for all impact categories, followed by activation, carbonization, and transport. Amongst, the carbocatalyst from seaweed (EN-BDC) presented the highest environmental impacts for all indicators. The catalytic performance for bio-monophenols was further studied. All carbocatalysts showed the performance of promoting monophenols, especially phenol, 2-methyl-phenol and p-cresol in the bio-oil. Amongst, EN-BDC was the best for producing monophenols (total up to 54.64% of bio-oil). Furthermore, characterization of fresh and spent catalysts were carried out to investigate the difference and evolution of surface functional groups before and after reactions. The catalytic activity of carbocatalyst was mainly owing to its mesoporous structure and abundant surface oxygen-containing functional groups, especially hydroxyl groups, which was also confirmed by employing the density functional theory.